TGF-β antisense oligonucleotides reduce mRNA expression of matrix metalloproteinases in cultured wound-healing-related cells - Philipp, Katrin; Riedel, Frank; Germann, Günter; Hörmann, Karl; Sauerbier, Michael (International journal of molecular medicine, 2005)
The pathology of chronic dermal ulcers is characterized by excessive proteolytic activity which degrades extracellular matrix. The transforming growth factor-β (TGF-β) has been identified as an important component of wound healing. Recent developments in molecular therapy offer exciting prospects for the modulation of wound healing, specifically those targeting TGF-β. We investigated the effect of TGF-β antisense oligonucleotides on the mRNA expression of matrix metalloproteinases in cultured human keratinocytes, fibroblasts and endothelial cells using multiplex RT-PCR. The treatment of keratinocytes and fibroblasts with TGF-β antisense oligonucleotides resulted in a significant decrease of expression of mRNA of MMP-1 and MMP-9 compared to controls. Accordingly, a decreased expression of MMP-1 mRNA in endothelial cells was detectable. Other MMPs were not affected. Affecting all dermal wound-healing-related cell types, TGF-β antisense oligonucleotide technology may be a potential therapeutic option for the inhibition of proteolytic tissue destruction in chronic wounds. Pharmaceutical intervention in this area ultimately may help clinicians to proactively intervene in an effort to prevent normal wounds from becoming chronic.